New Critical Nitrogen Curve Based on Leaf Area Index for Winter Wheat. (1st March 2014) - Zhao, Ben; Yao, Xia; Tian, YongChao; Liu, XiaoJun; Ata-Ul-Karim, Syed Tahir; Ni, Jun; Cao, WeiXing; Zhu, Yan
Abstract : Accurate forecasting of N required for plant growth can help optimize grain yields, farm profits, and N use efficiency and reduce the risk of environmental pollution. The objectives of this study were to: (i) establish a critical N ( N c ) dilution curve for winter wheat ( Triticum aestivum L.) based on the leaf area index (LAI), (ii) compare this curve with N c dilution curves for winter wheat that are based on plant dry matter, and (iii) assess the plausibility of using this new curve to estimate the N status of winter wheat. Four field experiments were conducted with different N application rates. Twenty plants from each plot were sampled from the Feekes 3 to the Feekes 10.5 stage for growth analysis. The relationship between N c and LAI could be described by a negative power equation, N c = 4.06LAI −0.4, when the LAI values were in the range of 1.4 to 7.5. For LAI values <1.4, however, the constant value N c = 3.58% was used. The N nutrition index (NNI) ranged from 0.34 to 1.31 during the vegetative stage under different N application rates from 2009 to 2011. There was a significant positive relationship between differences in NNI and differences in N application rates across four wheat development stages. Validation of the models with independent data produced a root mean squared error of 28 kg ha −1 . The N c dilution curve identified limiting and nonlimiting wheat N status and could be used as a reliable indicator of in‐season N stress of wheat grown in eastern China.